Extraction Of Carotenoid Compounds From Watermelon Pulp With Microemulsion Based Technique: Optimization Studies - Inan-Cinkir, Nuray; Agcam, Erdal; Altay, Filiz; Akyildiz, Asiye (Aperta, 2022)
The application of two microemulsion based extraction methods (Extraction-1 and Extraction-2) were investigated for the extraction of carotenoids from watermelon pulp in the present study. Span 20 and glycerol for Extraction-1, and sucrose monopalmitate (SMP) with salt (NaCl) for Extraction-2 demonstrated the highest extraction efficiency. Optimization studies by response surface methodology were applied to these conditions. The optimum conditions were conducted as 6.025 g/g of Span 20/pulp sample-(S), 8.827 of glycerol/S, 38.75 degrees C of temperature and 18.75 min of time; 1.13 g/g of SMP/S, 7.53 g/g of Salt/S, 66.25 C and 46.3 min of temperature and time for Extraction-1 and Extraction-2, respectively. The extraction efficiency for the optimum conditions were determined as 96.5% and 83.6% for Extraction-1 and Extraction-2, respectively. The results showed that the proposed methods can be successfully performed in the extraction of carotenoids from watermelon pulp compared to conventional solvent extraction.